Racismo, preconceito e discriminação: concepções de professores - Santos, Risomar Alves dos (2007)
This study has the objective to apprehend how last year undergraduate students of a Pedagogy course, in the city of São Paulo, understand racism, prejudice and discrimination in teacher education and professional development. The theoretical framework was based on teacher education researchers, such as: André (1999), Candau (2002), Imbernón (2002), Garcia (1999) as well as on researchers who discuss racism and discrimination, such as: Guimarães (2002), Cavalleiro (2003), Munanga (1999) and Jones (1973). The methodological procedures included: a questionnaire in the beginning of the study, field notes and an intensive interview with a simulation teaching case. The content analysis made it possible to organize data in three topics: the participants´ view of racism; education for the diversity; underlying conceptions about the diversity: the place of black race. The results disclosed that the participants have a critical view of racism, prejudice and discrimination, understanding them as barrier to respectful relations between the many social groups. They suggest that education and education for the diversity may be the human solution to valuation of different cultures and groups. Further, they emphasize racist behavior still persisting in the 21st century is unacceptable . My conclusion at the end of this research is that we still have a long way to achieve an educational system that is built upon equality, in which becomes possible the construction of a multi-cultural and multi-racial society